Metody interwencyjne dużych grup - Grzybowska, Katarzyna; Grzelczak, Agnieszka (Large group interventions methods, 2005)
Modem enterprises operate on a global and competitive market, in an ever-changing environment. Thus new trends in changes and project management appear. Transformation, reorganization or restructuring are the creation and change of a whole new form, function or structure of a firm. Transformation or reorganization are to create a company that is better than before. Project of organization transformation is therefore the profound change of the organization as a whole, not just part of it. The article is a discussion about Large Group Interventions methods (LGI). The term large group interventions was invented in the early 1990s by B.T. Alban and B.B. Bunker, two US-based organizational consultants and academics. Large Group Interventions methods are a label that is applied to many different methods of getting a crowd to come to consensus but not only. The LGI methods are used in Project Change Management. Although there are more than twenty different Large Group Interventions methods. This paper will focus on four of them: Open Space Technology, Future Search, Real Time Strategic Change and Appreciative Inquiry. A lot of the organizations used LGI methods: 3M, Boeing, Ford Motor Company, Guinness, KPMG, Marriott Hotels, Microsoft and Shell.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 573-579